Influência do hipotireoidismo gestacional experimental em sistemas biológicos centrais de regulação da nocicepção em ratos - Alves, Iura Gonzalez Nogueira (2016)
Changes in maternal thyroid hormones concentrations during pregnancy can affect the body development of pups. However, despite the recent race for the understanding of the mechanisms that explain the impact of perinatal life in the occurrence of different diseases, little has been done to investigate the role of maternal thyroid hormones for proper development of CNS structures, important in regulating perception nociceptive. In this sense, in the present study we investigate the effect of experimental gestational hypothyroidism (EGH) in biological systems of nociceptive circuitry. The EGH was induced by methimazole to 0.02% in drinking water from ninth day of gestation until delivery. The threshold for noxious temperature was evaluated by using the hot plate apparatus (52 ± 0.2 ° C) in male offspring from methimazole treated dams (OMTD) and offspring from water treated dams (OWTD), on postnatal day (PND) 60 days, in baseline condiction and after a drug injection (morphine, memantine, sertraline and AMPT). In addition, thyroid status was evaluated through the determination of total T3 and T4 serum levels on PND 60, sections through the vlPAG were processed for TH immunofluorescence, the contents of glutamate in the cerebrospinal fluid was measured and evaluated oxidative parameters in spinal cord. The results were expressed mean ± Standard Error values. Three and two way ANOVA, Student t test, Mann-Whitney and correlation test were used. The threshold of statistical significance was set at p<0.05. Thus, our data showed that EGH does not generate significant impact on the treated mothers when they are compared to control, but in the offspring important effects of lack of maternal THs in the intrauterine period were observed. OMTD had less body weight after 60 DPN (p <0.01), higher serum concentration of TT3 (p <0.05), higher analgesia on the hot plate after i.p. morphine, at times 30 and 60 minutes (time factor interaction and treatment (F (4, 80) = 2.50, p <0.05) and increased lipid peroxidation (assessed by quantification of TBARS) in the spinal cord (p <0.01 ). Given the above, we conclude that the lack of THs during pregnancy causes changes in body weight and serum concentrations of T3, as well as in biological systems of nociceptive circuitry.